A mutation (L1014F) in the voltage‐gated sodium channel of the grain aphid, Sitobion avenae, is associated with resistance to pyrethroid insecticides. Issue 8 (12th December 2013) - Foster, Stephen P; Paul, Verity L; Slater, Russell; Warren, Anne; Denholm, Ian; Field, Linda M; Williamson, Martin S
Abstract BACKGROUND The grain aphid, Sitobion avenae Fabricius (Hemiptera: Aphididae), is an important pest of cereal crops. Pesticides are the main method for control but carry the risk of selecting for resistance. In response to reports of reduced efficacy of pyrethroid sprays applied to S. avenae, field samples were collected and screened for mutations in the voltage‐gated sodium channel, the primary target site for pyrethroids. Aphid mobility and mortality to lambda‐cyhalothrin were measured in coated glass vial bioassays. RESULTS A single amino acid substitution (L1014F) was identified in the domain IIS6 segment of the sodium channel from the S. avenae samples exhibiting reduced pyrethroid efficacy. Bioassays on aphids heterozygous for the kdr mutation (SR) or homozygous for the wild‐type allele (SS) showed that those carrying the mutation had significantly lower susceptibility to lambda‐cyhalothrin. CONCLUSION The L1014F (kdr) mutation, known to confer pyrethroid resistance in many insect pests, has been identified for the first time in S. avenae. Clonal lines heterozygous for the mutation showed 35–40‐fold resistance to lambda‐cyhalothrin in laboratory bioassays, consistent with the reported effect of this mutation on pyrethroid sensitivity in other aphid species. © 2013 Society of Chemical Industry